Modulation of the electronic and spectroscopic properties of Zn(II) phthalocyanines by their substitution pattern - Topal, Sevinc Z.; Isci, Umit; Kumru, Ufuk; Atilla, Devrim; Gürek, Ayşe Gül; Hirel, Catherine; Durmuş, Mahmut (Royal Soc Chemistry, 2014)
Four isomerically pure octasubstituted zinc phthalocyanines with variations in the attachment atom and positions of the substituents were selected for a systematic investigation of the effect of the substitution pattern on their electronic and spectroscopic properties. Effects which were investigated are the position, the electron donating and withdrawing properties, and the donating force of the substituent. The results are discussed and interpreted based on theoretical and experimental determination of the orbital levels. This work allows us to highlight which substitution patterns are the most suitable considering different common applications of phthalocyanines.
Keywords: Oxygen Quantum Yields; Photochemical Properties; Metal-Free; Sensitizer Candidates; Photodynamic Therapy; Organic-Solvents; Fluorescence; Zinc; Photosensitization; Derivatives